The Use of Management Control Systems and Operations Management Techniques - Edelcio Koitiro Nisiyama; José Carlos Tiomatsu Oyadomari; Chen Yen-Tsang; Andson Braga de Aguiar (BBR: Brazilian Business Review)
It is well known that both management control systems (MCSs) and operations management (OM) are related to firm performance; however, an integrated st udy that involves MCS and OM within the context of firm performance is still lacking. This research aimed to examine the relationships among the use of MCSs and OM techniques and firm performance in the Brazilian auto parts industry. Simons’ levers of cont rol framework was used to characterise the uses of MCSs, and OM techniques, such as total quality management (TQM) and continuous improvement programmes, were adopted. The results obtained through the structural equation modelling indicated that the diagno stic use of MCSs is positively associated with the goals of cost reduction. In addition, the interactive use of MCSs is positively associated with the objectives of introducing new products, which is consistent with previous research. Additionally, OM tech niques are positively related to cost reduction but have no direct relationship with the introduction of new products.